RUNX3 Methylation: An Epigenetic Biomarker for Early Liver Damage Induced by Co-Exposure to Aflatoxin B1 and Hepatitis B Virus - Yunying Mo; Xiaodan Lu; Shixiong Zheng; Junfeng Deng; Shihan Huang; Ye Hong; Xiaoyu Xian; Aliya Yijiati; Xingyu Yu; Xunwu Luo; Miner Xiao; Xingfen Yang; et al. (Toxics)
Aflatoxin B1 (AFB1), a well-established hepatic carcinogen, has limited research on early-stage epigenetic biomarkers for aflatoxin-induced liver damage. In this study, we investigated 168 unpackaged peanut oil (UPP) consumers to evaluate associations among AFB1 exposure, HBV infection, RUNX3 methylation, and liver function. Our findings indicated an average daily AFB1 intake of 3.14 ng/kg·bw/day from UPP oil consumption. The high AFB1 exposure group exhibited significantly elevated gamma-glutamyl transferase (GGT) levels compared with the low AFB1 exposure group (p = 0.030). AFB1 exposure was negatively correlated with methylation status at the 2nd, 8th, and 9th CpG sites of RUNX3 (rs = −0.196, −0.192, −0.181, p = 0.021, 0.024, 0.036). Furthermore, methylation at the 8th and 9th CpG sites positively correlated with GGT (rs = 0.206, 0.203, p = 0.019, 0.024). HBV infection significantly influenced RUNX3 methylation, with the HBsAg+ group exhibiting 16.25% lower methylation (p < 0.05). Stratified analysis by HBV and AFB1 revealed that in the low AFB1 exposure subgroup, RUNX3 methylation in the HBsAg+ group exhibited a significant 26.38% reduction compared with the HBsAg− group. These results indicated that AFB1 and HBV independently and synergistically promote site-specific RUNX3 hypomethylation. Our results implicated RUNX3 methylation as a critical mediator in HBV-AFB1 co-exposure hepatotoxicity, potentially serving as a novel epigenetic biomarker for early liver damage detection.